Penyuluhan Deteksi Gangguan Bipolar pada Remaja di Masyarakat Pesisir Baubau - Iin Handayani; Harlina Harlina; Abdul Manaf; La Ode Maman (Jurnal Pengabdian Masyarakat Nusantara, 2021)
Bipolar disorder is a mental health condition characterized by extreme mood swings between manic and depressive episodes. Coastal communities often face limited access to mental health information and services, leading to a lack of awareness and early detection of this disorder. This community service program aims to enhance awareness and understanding of bipolar disorder among adolescents in the coastal area of Baubau City through a community-based counseling approach. The methods used in this program include socialization, interactive discussions, case simulations, as well as pre-test and post-test evaluations to measure program effectiveness. The results showed that after attending the counseling session, participants' understanding of bipolar disorder increased by 85%, while the community's readiness to seek professional help increased from 30% to 75%. Additionally, positive social changes occurred, such as reduced stigma against mental disorders and the emergence of community leaders who actively promote mental health education. These findings indicate that a community-based educational approach can be an effective strategy in improving mental health literacy, particularly in areas with limited access to psychological services. Therefore, it is recommended that continuous counseling programs and further collaborations between the government, healthcare professionals, and local communities be implemented to ensure the sustainability of this program.